(untitled) (Diyala Journal of Engineering Sciences, 2016)
This research is devoted to study the effect of adding alloying elements (Ti and Sn) with different percentages (1, 3 and 5) wt% on the microstructure, mechanical properties, and dry sliding wear resistance of Al-6.9wt%Si-1.7%Cu alloy. The particle size of Ti powder is 200 µm, but the Sn adding as a small bits to the alloy. The microstructures were examined with optical microscope for the base alloy before and after adding alloying elements. This examination showed that the changing occurs on the morphology of grain, precipitated intermetallic compounds and other phases (TiAl, TiAl2, Al2Cu and β-Sn) determined by the x-ray diffraction. The mechanical properties studied in this research were the tensile strength, impact toughness, and hardness. The results depicted that the ơu, ơy and hardness increase with increasing the percentage of Ti, while they decrease with increase the percentage of Sn. On the other hand, the alloys with Ti additions revealed that El% decrease with increasing Ti additions, but El% increase with increasing the Sn addition to the base alloy. Also, the impact toughness, was examined, and it was found alloying element was lower than the base alloy for both elements (Ti and Sn). The pin-on-disk technique was used to determine the wear resistance for base alloy before and after adding the alloying elements. The wear resistance increased with increasing the percentage of the Sn, but it decreased with increasing the percentage of Ti at different applied loads (2.5, 5 and, 7.5) N at a constant sliding speed of (3.7) m/sec.